An Assessment of Factors Responsible for Low Voter Turnout in Nigeria: A Literature Review - Oyoru, Rashida Adamu (Kashere Journal of Politics and International Relations, 2023)
Nigeria gained independence in 1960 but became full-fledged democracy in 1999 after several years of military intervention in the political sphere of the country. The first republic was between 1960-1966 followed by the second republic which took place between 1979-1983; the third republic was later established in 1993 following a presidential election that was largely regarded as free and fair but was later nullified by General Ibrahim Babangida which prevented the president-elect, Moshood Abiola, from assuming office. The need to involve citizens in the business of governance is one of the reasons that inform the modern democratic thinking. There have been steady decline in voter turnout since 2003 general election to the 2019 presidential election in Nigeria. The major objective of this study is to review literature on the factors responsible for voter turnout in Nigeria. To achieve the aim of this study, the study adopted content analysis of secondary data and relied on secondary data as source of data for the study. The study concluded that the main causes of low voter turnout in Nigerian elections include but not limited to the following; the failure of elected officials to fulfill their campaign promises, poor civic education among other things. The study recommended among other things that the Independent National Electoral Commission (INEC) should be impartial and free of political influence by refusing to associate with any political party before, during and after the election.